2022
DOI: 10.54393/pbmj.v5i6.525
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Voice Changes during Covid-19 Infections: A Retrospective Study

Abstract: Communication is defined as the phenomenon found specifically in animal species. It was however refined and modified only by the human species. Language and speech are two basic areas that fall under the umbrella of communication. With these processes also comes the impending danger of abnormal speech and language, leading to the development of their disorders. Objectives: Reporting the frequency changes in the voice of patients who are positive of covid-19. Methods: Application of cross-section study type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(1 reference statement)
1
0
0
Order By: Relevance
“…This study was a crosssectional study, the data was collected during the time the individuals were infected whereas my study was a retrospective study and the data was collected after the recovery of the Covid-19 patients. The results of the study carried out by Deshmukh and colleagues indicated that voice ow changes were observed in infected patients which is similar to the results of my study as well, that showed that voice changes were observed in infected patients most of the time during the infection [28] C O N C L U S I O N participants' voices went through a change and had become relatively weaker and shakier than their normal healthy voice. it was also proved that voice change after its use for the entire day was also commonly noted issue in the subjects involved.…”
Section: E T H O D Ssupporting
confidence: 87%
“…This study was a crosssectional study, the data was collected during the time the individuals were infected whereas my study was a retrospective study and the data was collected after the recovery of the Covid-19 patients. The results of the study carried out by Deshmukh and colleagues indicated that voice ow changes were observed in infected patients which is similar to the results of my study as well, that showed that voice changes were observed in infected patients most of the time during the infection [28] C O N C L U S I O N participants' voices went through a change and had become relatively weaker and shakier than their normal healthy voice. it was also proved that voice change after its use for the entire day was also commonly noted issue in the subjects involved.…”
Section: E T H O D Ssupporting
confidence: 87%